Multiply 7 x 12 which is 84, 8x2 is 16, 16 divded by 3 is 5, so 5 minutes
15.49x = 13.99x + 6
15.49x - 13.99x = 6
1.50x = 6
x = 6 / 1.50
x = 4 <=== u can buy 4 DVD's for the same amount
15.49 * 4 = 61.96
13.99(4) + 6 = 61.96
Answer: x = 4 and x = -3/2
Procedure:
1) Given: 2x^2 - 5x - 12 = 0
2) Multiply both sides by : 2(2x^2) - 2(5x) - 2(12) = 0
3) Rearrange: (2x)^2 -5(2x) - 24 = 0
4) Notice that the common factor is (2x)
5) Set the parenthesis with the common factor inside:
(2x ) (2x ) =0
6) The first sign is the same sign of the second term of the trinomial, which is negative, the second sign is the product of the signs of the second and the third terms of the polynomial, which is (-)*(-) = + (positive)
(2x - )(2x + ) = 0
7) find two numbers that sum up - 5x and its product is -24.
- 8 + 3 = - 5
(-8)(+3) = -24
=> the numbers in the factors are -8 and +3
(2x - 8) (2x + 3) = 0
That is the factored equation. Now you can solve
8) a) 2x - 8 = 0 => 2x = 8 => x = 8/2 => x = 4
b) 2x + 3 = 0 => 2x = - 3 => x = - 3/2
Answer: the two solutions are x = 4 and x = -3/2
As shown:
Angle C = Angle f = 127
The length of fe = the length of CA = 2 units
Angle E = Angle A = 40
So, triangle ABC = triangle EDF by ASA
The answer is option 2